In Situ Raman Spectroscopy of the Type Selective Etching of Carbon Nanotubes and Their Growth from C60 Seeds - Li-Pook-Than, Andrew (Université d'Ottawa / University of Ottawa, 2015)
In situ Raman spectroscopy was used to explore etching of carbon nanotubes as well as their growth from C60. The thesis is in three parts: (1) C60 seed particles were partially oxidized in air and were used to grow carbon nanotubes and other nanocarbon structures. Seed oxidization was characterized by monitoring the evolution of the Raman Ag(2) peak and the D band, and oxidation temperature was found to be critical to nanotube growth. (2) To further explore oxidation, carbon nanotubes were thermally oxidized in air at different temperatures, while the evolution of different Raman bands was tracked. Etching dynamics and band intensity evolution were tracked in situ. Notably, metallic species were found to etch much more rapidly than semiconducting species of similar diameter. (3) To confirm and expand on this, a novel, simultaneous two-laser Raman spectroscopy setup was used to track the thermal oxidation of carbon nanotubes in O2 and CO2 gases at different temperatures. Metallic species were resonant with one laser line, while semiconducting species were resonant with the other, so changes to sample metallicity could be tracked unambiguously in two separate spectra. Again, metals were found to etch more rapidly. In situ Raman spectroscopy can track the evolution of nanotubes in real time and provide insight into processing. In general, detailed process monitoring like this can help in the development of selective synthesis and processing.
Keywords: Carbon nanotubes; Raman spectroscopy; Oxidation; Fullerenes; Nanostructures; Chemical vapor deposition; Metallicity; In situ technique